Excavations by the American School at the Theatre of Sikyon. - McMurtry, W. J. (Analecta Gorgiana, 2009)
McMurtry's original site report on the excavation of the Theater of Sikyon near Corinth. Sikyon (or Sicyon) boasts a well preserved Greek theater whose excavation illuminates the structures which supported Greek drama